A Balanced Approach to Building STEM College and Career Readiness in High School: Combining STEM Intervention and Enrichment Programs - Sladjana S. Rakich; Vinh Tran (Lectito Journals, 2016)
Often STEM schools and STEM enrichment programs attract primarily high achieving students or those with strong motivation or interest. However, to ensure that more students pursue interest in STEM, steps must be taken to provide access for all students. For a balanced and integrated career development focus, schools must provide learning opportunities that are appropriate for all students. This paper outlines two approaches to the creation of a comprehensive STEM College and Career development pathway in high schools.